(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2026)
The current research was conducted to assess some key water quality parameters of Kaptai Lake (KL). To do this, water samples were collected from seventeen sites in the month of March, followed by laboratory assessment and multivariate analyses. The results revealed that pH, electrical conductivity (EC), temperature, dissolved oxygen (DO), biological oxygen demand (BOD), free carbon di-oxide (CO2), bi-carbonate (HCO3⁻), chloride (Cl⁻), and calcium (Ca2+) varied with the range of 6.58-7.84, 111-127 µS/cm, 25- 26 °C, 9.10-10.20 mg/L, 2.0-5.90 mg/L, 88-180 mg/L, 214-390 mg/L, 89-231 mg/L and 0.25- 0.54 mg/L with mean values of 7.50, 117 µS/cm, 25.36°C, 9.64 mg/L, 4.02 mg/L, 139.06 mg/L, 295.71 mg/L, 159.18 mg/L and 0.31 mg/L, respectively. Water quality parameters exhibited diverse distributions and variability: pH was negatively (-1.49) skewed and EC was positively (1.23) skewed, while temperature and DO were approximately normally distributed with skewness of -0.07 and -0.04, respectively. The BOD, free CO2, HCO3⁻, Cl⁻, and Ca2+ showed moderate to high variability with skewness of -0.32, -0.29, 0.57, 0.13 and 2.40, respectively. The inverse distance weighted (IDW) interpolation of each parameter showed almost uniformity across the sampling sites. The hierarchical clustering dendrogram and correlation matrix heatmap revealed distinct groupings among variables: EC was correlated strongly with ionic constituents (HCO3⁻, Cl⁻, Ca2⁺), while BOD, free CO2, and temperature were inversely correlated with DO and pH. Although most parameters meet the criteria for irrigation and fisheries, relatively high values ​​of BOD at certain locations indicate local anthropogenic impacts. These results emphasize water quality across KL and highlight the need for mitigation measures to ensure sustainable aquaculture and irrigation practices. Int. J. Agril. Res. Innov. Tech. 15(2): 138-146, Dec 2025